PERANCANGAN LEARNING MANAGEMENT SYSTEM (LMS) PADA SMAN 10 BEKASI - Marisa; Sabar Hanadwiputra (POLITEKNIK PIKSI GANESHA, 2019)
Developments in the world of information technology is increasingly rapidly. The use of information technology has spreadin to all fields, including geducation. E-Learning is an example of the use of information technology in education. Application of E-Learning increasingly facilitated by the LMS (Learning Management System) that provides aplatformthathas been integrated for the contents,direction and a learning management systemas aconvenience for users include students, content creators, and administrators. Moodle LMS isused inthe manufacture ofE-Learning at SMAN10 Bekasi is not applied learning based E-Learning. Manufacture of E-Learning is expected to help improve the teaching and learning processin SMAN 10 Bekasi, E-Learning will then be attempted by students of SMAN10 Bekasi. By getting thestudents' perceptions regarding the implementation of E-Learning inconventional educational models, especially in SMAN 10 Bekasi